Immune variations throughout the course of tuberculosis treatment and its relationship with adrenal hormone changes in HIV-1 patients co-infected with Mycobacterium tuberculosis - Vecchione, María Belén (Tuberculosis (Edinb), 2021)
HIV infection is a major risk factor predisposing for Mycobacterium tuberculosis infection and progression to active tuberculosis (TB). As host immune response defines the course of infection, we aimed to identify immuno-endocrine changes over six-months of anti-TB chemotherapy in HIV+ people. Plasma levels of Cortisol, DHEA and DHEA-S, percentages of CD4+ regulatory T cell subsets and number of IFN-γ-secreting cells were determined. Several cytokines, chemokines and C-reactive protein levels were measured. Results were correlated with clinical parameters as predictors of infection resolution and compared to similar data from HIV+ individuals, HIV-infected persons with latent TB infection and healthy donors. Throughout the course of anti-TB/HIV treatment, DHEA and DHEA-S plasma levels raised while cortisol diminished, which correlated to predictive factors of infection resolution. Furthermore, the balance between cortisol and DHEA, together with clinical assessment, may be considered as an indicator of clinical outcome after anti-TB treatment in HIV+ individuals. Clinical improvement was associated with reduced frequency of unconventional Tregs, increment in IFN-γ-secreting cells, diminution of systemic inflammation and changes of circulating cytokines and chemokines. This study suggests that the combined anti-HIV/TB therapies result in partial restoration of both, immune function and adrenal hormone plasma levels.